Vietnamese Teachers’ Perspectives of CLIL in Primary Schools – Promoting Lifelong Learning and Questioning over Inclusive Education and Teachers’ Intercultural Competence: A Qualitative Study - Hà, Tú Anh; Gómez Parra, María Elena (Verbum, 2024)
This article explores teachers’ perspectives of CLIL in Vietnamese context by using a semi-structured interview with six teachers coming from two private primary schools in Hanoi, Vietnam. Findings of the paper point out both positive and negative points of CLIL in primary schools. Due to the fact that CLIL embraces culture as one of its 4Cs, it can help students to relate what they learn to the reality (i.e., meaningful learning). Hence, CLIL is a practical educational approach to facilitate students’ deeper learning, which is the foundation of lifelong learning. CLIL also helps teachers to manage the tempo of the class as well as lower the anxiety of students by preparing them with enough language for the content. However, there is concern over the content to support students’ pleasure of learning a foreign language. This poses a question of choosing and exploiting the content to make an inclusive CLIL classroom, which might need to be tailored to students’ interest and strengths. In addition, content and language teachers are required to have lifelong learning ability and intercultural communicative competence to collaborate with each other and apply CLIL effectively.